2015
DOI: 10.1007/s10071-015-0899-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the perceptual origin of right-sided feeding biases in cetaceans

Abstract: Foraging behaviour of many cetacean species features the side biases at the population level. The origin of these behavioural lateralisations remains generally unclear. Here we explored lateralisation in aerial display of resident orcas in different behavioural contexts. Side preferences were analysed in lunging during foraging and breaching. One event of each type of displays per individually identified orca was used for analysis. Orcas showed a population-level preference to lunge on the right side when fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 22 publications
4
37
0
Order By: Relevance
“…Findings in Karenina et al, 2017 demonstrates that lateralization regarding spatial position near the mother in young occurs in a diverse range of vertebrate species [ 11 ]. Other mother/calf cetacean lateralization studies have been presented for beluga whales [ 13 , 14 ] and killer whales [ 15 , 16 ] with similar findings; these studies showed that social behaviors correspond to the right brain hemisphere and foraging behavior corresponds to the left brain hemisphere. Findings from a laterality study conducted on adult wild Indo-Pacific bottlenose dolphin ( Tursiops aduncus ) found that during inquisitive approaches to a human observer (diver), the dolphin used the left eye significantly more frequently than the right eye, and rubbing was conducted significantly more frequently with the left flipper than with the right flipper [ 17 ].…”
Section: Introductionsupporting
confidence: 68%
“…Findings in Karenina et al, 2017 demonstrates that lateralization regarding spatial position near the mother in young occurs in a diverse range of vertebrate species [ 11 ]. Other mother/calf cetacean lateralization studies have been presented for beluga whales [ 13 , 14 ] and killer whales [ 15 , 16 ] with similar findings; these studies showed that social behaviors correspond to the right brain hemisphere and foraging behavior corresponds to the left brain hemisphere. Findings from a laterality study conducted on adult wild Indo-Pacific bottlenose dolphin ( Tursiops aduncus ) found that during inquisitive approaches to a human observer (diver), the dolphin used the left eye significantly more frequently than the right eye, and rubbing was conducted significantly more frequently with the left flipper than with the right flipper [ 17 ].…”
Section: Introductionsupporting
confidence: 68%
“…These subdivisions of function have been determined by testing a range of non-human species, primarily but not exclusively domestic chicks [15], pigeons [16], zebra fish [17], sheep [18] and dogs [19]. Observation of some species in the wild has confirmed that these asymmetries are seen not only in laboratory settings but also in natural habitats; for example, in Australian magpies responding to a predator [20] and in cetaceans feeding with a right side bias [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some foraging behaviors of the bottlenose dolphin were also found to be lateralized, meaning a localization of function or activity on one side of the body in preference to the other (e.g., Silber and Fertl, 1995;Lewis and Schroeder, 2003). It was suggested that the observed right-sided lateralization in dolphins (but also whales) when foraging may be associated with the visual perception of prey (Karenina et al, 2016).…”
Section: Behavioral Data On Visionmentioning
confidence: 99%